The Role of Teachers in Forming Self-Regulation in Children with Moderate Autism Spectrum - Syafitri, Muthia; Rachelia, Ussy; Chi, Gabriel; Dariyo, Agoes (Journal of Social Science, 2024)
Self-regulation in children with moderate levels of autism, using a qualitative approach with a case study involving three shadow teachers in Tangerang. Results show that learning strategies, communicative support, independence training, and effective emotional control are key in developing self-regulation. Consistent teaching methods, real examples, and a patient and firm approach are very important. In conclusion, self-regulation in children with moderate levels of autism can be improved through appropriate learning strategies, communicative support, independence training, and effective emotional control, providing theoretical and practical contributions in the education of children with autism.